Macrófagos associados a tumores: um potencial alvo terapêutico em câncer de mama - Diego Carlos dos Reis (2018)
Tumor-associated macrophages (TAMs) representing most of the leukocyte population in the tumor microenvironment of breast cancer. TAMs can act on neoplastic development over different mechanisms depending on their activation status. Considering the evidence of the critical role of these cells in the tumor microenvironment, this work aimed to evaluate the role of TAMs on the metastatic progression of 4T1 mouse mammary carcinoma and spontaneous canine mammary carcinomas. Additionally, it was evaluated the immunomodulatory effects of thalidomide as a possible therapeutic target on TAMs polarization in mice inoculated with 4T1 mouse mammary carcinoma. The 4T1 cells were inoculated into female BALB/c mice to obtain the solid tumor and the animals were euthanized at different times of tumor progression (14th, 21st and 28th day of inoculation). Primary tumor and lung were collected for the evaluation of TAMs, versican expression, inflammatory mediators, tumor angiogenesis, and metastases. Forced spirometry technique was also performed to evaluate the mice’s pulmonary functions. Spontaneous canine mammary carcinomas samples were selected and evaluated for TAMs infiltration and versican expression. In a second experiment, 4T1 tumor-bearing mice received oral daily treatment of thalidomide at concentrations of 50 mg/kg, 100 mg/kg, and 150 mg/kg for 23 days. The results obtained demonstrate that TAMs infiltration and versican expression was associated to low-grade and advanced stages of canine mammary carcinomas. In mice, TAMs and versican shown higher in late stages of tumor progression and associated to increased inflammation and angiogenesis of the primary’s tumors, while in the lung TAMs infiltration was associated with pulmonary dysfunction due to the increased number of metastatic nodules, airways leukocytes influx, and high inflammatory mediators’ levels. In the lung, the administration of thalidomide at dose 150 mg/kg reduced the neoplastic proliferation and the numbers of metastatic nodules associated to an increase in inflammation with higher number of TAMs. In conclusion, TAMs appear to play a critical role in the metastatic progression of breast cancer, the immunomodulatory effect of thalidomide may be a therapeutic option for this disease.